2019
DOI: 10.7567/1882-0786/ab14be
|View full text |Cite
|
Sign up to set email alerts
|

Recombination activity of sub-grain boundaries and dislocation arrays in quasi-single crystalline silicon

Abstract: Crystallographic defects in quasi-single crystalline (QSC) silicon are seriously detrimental to the performances of solar cells. In this work, we have identified these crystallographic defects as sub-grain boundaries (sub-GBs) and dislocation arrays (DAs). Sub-GBs with misorientation of >0.7° always show strong recombination activity, which are the main cause for the efficiency degradation of solar cells. Moreover, the recombination activity of sub-GBs with misorientation of <0.7° and DAs is strongly dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[36] Sub-GBs, though with a small deviation of crystalline lattice orientation, usually cause distorted regions [13,21] which could attract impurity precipitating and result in dislocation generation, significantly decreasing the minority carrier lifetime because of their strong recombination activity. [37][38][39] Lantreibecq et al [40] observed sub-GBs with TEM and SEM. They found that sub-GBs were constituted by a set of dense, perfectly organized immobile dislocations aligned along the growing direction and having an edge character.…”
Section: Subgrain Boundariesmentioning
confidence: 99%
“…[36] Sub-GBs, though with a small deviation of crystalline lattice orientation, usually cause distorted regions [13,21] which could attract impurity precipitating and result in dislocation generation, significantly decreasing the minority carrier lifetime because of their strong recombination activity. [37][38][39] Lantreibecq et al [40] observed sub-GBs with TEM and SEM. They found that sub-GBs were constituted by a set of dense, perfectly organized immobile dislocations aligned along the growing direction and having an edge character.…”
Section: Subgrain Boundariesmentioning
confidence: 99%
“…GB is another dominant lifetime-limiting defect in multi-and cast-mono crystalline silicon. In general theory, GB can be For more details of SA GB, Mao et al [89] provided some information about its recombination activity. They investigated the recombination activities of SA GB in cast mono silicon (CM-Si) and found that the recombination activity of SA GB increased with the mis-orientation angle and saturated at the mis-orientation angle above 0.7 • , as shown in figure 15.…”
Section: Passivation Of Grain Boundarymentioning
confidence: 99%